The adsorption of chelating reagents on oxide minerals - Bryson, Michael Andrew Walker (Rhodes University, Faculty of Science, Department of Chemistry, 1986)
This work constitutes a fundamental study of the interaction between chelating reagents and oxide minerals . The adsorption mechanisms have been elucidated for most of the systems generated by the oxides of copper(II) or iron(III) and chelating reagents octyl hydroxamate, N-phenylbenzohydroxamate, salicylaldoxime, 5-nitrosalicylaldoxime or 8-hydroxyquinoline. The results of the preliminary work on one of the systems, viz. the oxide-hydroxamate system, indicated that the classical type adsorption process, in which the reagent forms a uniform layer of chelate over the oxide surface was not applicable. Rather, the adsorption occurred via the formation of a discrete metal-chelate precipitate at the oxide surface. In order to better understand the associated with copper (II) oxide, adsorption process the oxide was recrystallized to produce a coarser material with a more uniform surface. This allowed the oxide surface to be viewed under the scanning electron microscope and also enabled the relative concentration of "surface" and "bulk" chelate to be assessed. A detailed investigation of the effect of the system variables; pH, conditioning period, concentration, temperature, surface area and dispersing reagent on the rate of precipitation of the copper chelate species of general form, Cu(chel)2' was made. In addition the chemical nature of the adsorbed species and the structural form of the precipitates were determined with the aid of infra-red spectroscopy and the scanning electron microscope. On the basis of these results a model has been formulated for the adsorption processes. In this model the adsorption dissolution, is considered to occur in stages: 1. Oxide dissolution, 2. metal complex formation, 3. Metal chelate precipitation at the oxide surface and 4. "bulk" chelate formation by post-precipitation processes. The precipitation process was examined in more detail by the study of the adsorption of chelate on copper metal. The results of this study showed that it was possible to relate the structural type of precipitate formed, ie. fibrous or platelike, to the degree of supersaturation of the metal complex in solution. Furthermore, it was found that the precipitate structure determined whether it remained attached to the surface or detached. Contact angle measurements of air bubbles on copper metal conditioned with chelate were related to the adsorption results in an attempt to isolate the optimum conditions for flotation of oxide minerals.
Keywords: Uncatalogued